THERMOPHYSICAL PROPERTIES OF LIQUID BINARY Mg-BASED ALLOYS - Plevachuk, Yuriy; Sklyarchuk, Vasyl; Pottlacher, Gernot; Yakymovych, Andriy; Tkach, Olha (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The binary magnesium-based Al-Mg, Mg-Zn alloys are under intense consideration as favourable cast alloys for using in automotive and aircraft industry and other high-strength applications. Magnesium alloys, as the lightest structure alloys, have received increasing research interests due to their high specific strength, excellent damping property, good electromagnetic shielding, environmental friendly. Besides, the potential use of magnesium alloys in the field of electronic packaging, such as heat dissipation for light entropy dioxides (LEDs), has drawn new research interest, resulting from their excellent electrical and thermal transport properties. In this study some thermophysical properties (electrical and thermal conductivity and thermoelectric power) of liquid binary Al33.3Mg66.7, Mg47.6Zn52.4 and Mg33.3Zn66.7 (all in wt.%), as the most promising cast alloys to fabricate components for cars, aircraft and other complex engineering products, were studied. The obtained results are compared with literature experimental and calculated data.